164k views
2 votes
Find an equation of the tangent to the curve at the given point by both eliminating the parameter and without eliminating the parameter.x = 6 + ln(t), y = t2 + 3, (6, 4)

User Calvin Li
by
4.8k points

1 Answer

1 vote

Answer:


y=2x-8

Explanation:

The given parametric equation is;


x=6+ln(t),y=t^2+3

BY ELIMINATING THE PARAMETER

To eliminate the parameter we make
t the subject in one equation and put it inside the other.

We make
t the subject in
x=6+ln(t) because it is easier.


\Rightarrow x-6=ln(t)


\Rightarrow {e}^(x-6)=e^(ln(t))


\Rightarrow {e}^(x-6)=t

Or


t={e}^(x-6)

We now substitute this into
y=t^2+3.

This gives us;


y=(e^(x-6))^2+3.


\Rightarrow y=e^(2(x-6))+3.

We have now eliminated the parameter.

The equation of the tangent at (6,4) is given by;


y-y_1=m(x-x_1)

where the gradient function is given by;


(dy)/(dx)=2e^(2(x-6))

We substitute
x=6 into the gradient function to obtain the gradient.


\Rightarrow m=2e^(2(6-6))


\Rightarrow m=2e^0


\Rightarrow m=2

The equation of the tangent becomes


y-4=2(x-6)

We simplify to obtain


y=2x-12+4


y=2x-8

WITHOUT ELIMINATING THE PARAMETER

The given parametric equation is;


x=6+ln(t),y=t^2+3

For
x=6+ln(t)


(dx)/(dt)=(1)/(t)

For
y=t^2+3


(dy)/(dt)=2t

The slope is given by;


(dy)/(dx)=((dy)/(dt) )/((dx)/(dt) )


(dy)/(dx)=(2t )/((1)/(t) )


(dy)/(dx)=2t^2

At the point, (6,4), we plug in any of the values into the parametric equation and find the corresponding value for
t.

Notice that

When
x=6,
6=6+\ln(t)


6-6=\ln(t)


0=\ln(t)


e^0=e^\ln(t)


1=t

when
y=4,
4=t^2+3


4-3=t^2


1=t^2


t=\pm1

But the slope is the same when we plug in any of these values for t.


(dy)/(dx)=2(\pm1)^2=2

The equation of the tangent becomes


y-4=2(x-6)

We simplify to obtain


y=2x-12+4


y=2x-8

User Nikit Barochiya
by
4.5k points